Tertiary lymphoid structures predict the prognosis and immunotherapy response of cholangiocarcinoma - Shang, Taiyu; Jiang, Tianyi; Lu, Tao; Wang, Hui; Cui, Xiaowen; Pan, Yufei; Xu, Mengyou; Pei, Mengmiao; Ding, Zhiwen; Feng, Xiaofan; Lin, Yunkai; Li, Xin; et al. (Frontiers in Immunology, 2023)
Cholangiocarcinoma (CCA) is a malignant tumor of the biliary epithelium with a poor prognosis. The lack of biomarkers to predict therapeutic response and prognosis is one of the major challenges for CCA treatment. Here, we investigated the prognostic value and clinical relevance of tertiary lymphoid structures (TLS) in 471 CCA patients (cohort 1) who received surgery and were treated with standard chemotherapy after postoperative progression and 100 CCA patients (cohort 2) who received first-line chemotherapy combined with immune checkpoint inhibitors (ICIs) to prevent postoperative recurrence. Different maturity of TLS was evaluated using hematoxylin and eosin (H&E) and immunohistochemical (IHC) staining in CCA tissue sections. We found that the abundance and spatial distribution of TLS were significantly correlated with the prognosis and ICIs immunotherapy response of CCA patients. Interestingly, intra-tumoral TLS and peri-tumoral TLS play opposite roles in predicting the survival prognosis of CCA patients and the therapeutic effect of ICIs. Specifically, a high density of intra-tumoral TLS (T-score high) was significantly correlated with better prognosis and higher response to immunotherapy, whereas a high density of peri-tumoral TLS (P-score high) was associated with worse prognosis and lower response to immunotherapy. In addition, we also exploited the TLS signature of four genes including PAX5, TCL1A, TNFRSF13C, and CD79A, and found strong staining of these proteins in the TLS regions, suggesting that they are potential biomarkers for TLS identification. Our data show that TLS is highly organized in CCA, and the presence of intra-tumoral TLS is a positive prognostic factor for CCA, which provides a theoretical basis for the future diagnosis and treatment of CCA.